Consideraciones metodológicas de los juegos pequeños en el desarrollo de la velocidad de niños entre 10 y 12 años, de la Unidad Educativa Juan Montalvo - Gómez Sánchez, Luis Alexander (2022)
The present study was carried out with the intention of analyzing the incidence of the methodological considerations of small games in the development of the speed of children between 10 and 12 years old, from the Juan Montalvo Educational Unit, for which an investigation was developed from a quantitative approach since within the study two instruments were applied to collect data, on the one hand a survey with a questionnaire that allowed collecting data on the independent variable and on the other hand the 10 x 5 speed test that allowed collecting data on the variable dependent, the student population that was taken into account for the study was 30 students, 17 men and 13 women to which an intentional non-probabilistic sampling was applied and a sample of 15 students, 8 men and 7 women, was taken. to whom the instruments were applied, which yielded deficient results in terms of the development of the speed that these students have, for which reason The existence of the problem previously raised was observed and evidenced, therefore, a plan was developed with different types of small methodological games that allow the optimal development of speed.